2020
DOI: 10.3390/foods9060741
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics and Microbiological Quality of Broiler Chicken Pectoralis Major Muscle Subjected to Different Storage Temperature and Duration

Abstract: Storage temperature and duration plays an important role in meat processing. Observations in poultry processing plants have shown a serious deviation in storage condition compared to the recommended procedures. Furthermore, there is still a paucity of evidence on the effects of storage temperature and duration on meat quality and microbial population. The aim of this study was to determine the effects of different temperature and duration during storage on physico-chemical properties and microbiological qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Zhang and Ertbjerg [81] observed an increase in purge and cooking loss in pork loins that were frozen at −20 • C and then thawed. Similar findings were also observed in studies that evaluated WHC in frozen/thawed beef [50], lamb [54], and chicken [58]. Interestingly, the rate at which product temperature drops from −1 to −7 • C has been shown to influence the amount of water loss during thawing, with greater freezing rates during this range leads to less water loss [97].…”
Section: Water Holding Capacitysupporting
confidence: 79%
“…Zhang and Ertbjerg [81] observed an increase in purge and cooking loss in pork loins that were frozen at −20 • C and then thawed. Similar findings were also observed in studies that evaluated WHC in frozen/thawed beef [50], lamb [54], and chicken [58]. Interestingly, the rate at which product temperature drops from −1 to −7 • C has been shown to influence the amount of water loss during thawing, with greater freezing rates during this range leads to less water loss [97].…”
Section: Water Holding Capacitysupporting
confidence: 79%
“…Generally, the color parameters faded after 30 days of storage, but supplementation with BKH, RKH and WKH significantly maintained about 75% of color attributes. Ab Aziz, et al [ 91 ] found that all color parameters of chicken meat preserved at different temperature degrees decreased with the storage period. No available studies cast light on the changes in color parameters and sensorial traits of chicken meat samples supplemented with kidney bean protein hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we observed that drip loss and cook loss were significantly lower in BYC than that in Cobb500. Drip loss and cook loss reflect muscle water‐holding capacity (Ab Aziz et al., 2020). Additionally, drip loss has a negative association with color parameters (lightness and redness) (Gotardo et al., 2015).…”
Section: Discussionmentioning
confidence: 99%